The effects of urban sprawl on spatial planning: A case of Chitungwiza Municipality - Chiunya, Wimbai G. (Midlands State University, 2017)
The research aims at investigating the effects of urban sprawl on spatial planning. Many Local authorities in Zimbabwe are suffering the consequences of urban sprawls and illegal settlements. These consequences vary from being environmental, social, political or economic. The research will undertake a literature review of the wider topic and identifies a number of aspects that are likely to affect spatial planning. Information is obtained from Chitungwiza Municipality, a Local Authority under Harare Metropolitan Province, which in this case is the case study. The research defined urban sprawl and spatial planning, and identified the causes of urban sprawl. The research outlines the reasons why urban sprawls occur, the aim is to see if what was said in literature applies to the Zimbabwean context. The research also adopted a European overview, African overview, National over view and a local over view with the intention of fully comprehending issues of urban sprawls. The researcher also looked at the history of spatial planning in Zimbabwe. Pieces of legislation which have been guiding spatial planning since its inception were also identified. The last aspect is on the relationship which exists between urban sprawl and spatial planning. Both qualitative and quantitative techniques of using interviews and questionnaires are used to gather data. The research findings showed that urban sprawl has a number of negative effects on spatial planning, but a further research is required on the effectiveness of legal actions taken against perpetrators of illegal settlements. Lastly, recommendations to the National Government, MLG,PW&NH, other line Ministries, Chitungwiza Municipality, Policy Formulators and to Individuals where offered at the end of the research.